Penilaian Risiko Kesehatan Akibat Pajanan Mikroplastik Polyethylene Terephthalate (PET) dalam Air Minum Isi Ulang di Kelurahan Tamangapa, Makassar Menggunakan Metode Environmental Health Risk Assessment - Kasim, Setiawan; Dullah, Arif Atul Mahmuda; Budirman, Budirman; Putri, Vicky Milenia Ramadhina (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Microplastic contamination in drinking water has emerged as a global public health concern. This study aimed to analyze the exposure of microplastics, particularly polyethylene terephthalate (PET), in refillable drinking water using the Environmental Health Risk Assessment (EHRA) method. A total of 20 water samples were collected from refill stations in Tamangapa Village, Makassar City. Microscopic analysis identified 104 microplastic particles, predominantly in the form of fibers (line shape) with dominant colors of blue (39 items) and transparent (27 items). Fourier Transform Infrared (FTIR) spectroscopy confirmed the presence of PET as the major polymer, along with smaller amounts of polyethylene, polypropylene, and ethylene vinyl acetate. The concentration of microplastics varied between 0.001 mg/kg and 0.030 mg/kg. Exposure assessment involving 100 respondents revealed that average water intake was 210 mg/kg/day, with an exposure frequency of 350 days/year. Non-carcinogenic intake projections over 5–30 years indicated increasing exposure levels, with mean values ranging from 0.0040 to 0.0242 mg/kg/day, surpassing the reference dose (RfD = 0.0004 mg/kg/day). Risk characterization showed that the Risk Quotient (RQ) values consistently exceeded 1, ranging from 10.07 to 60.47, indicating an unacceptable health risk. Lower body weight was associated with higher susceptibility to microplastic toxicity. These findings highlight that long-term consumption of refillable drinking water contaminated with PET microplastics poses significant non-carcinogenic health risks to the local population. Strengthening monitoring systems, improving water treatment processes, and formulating targeted public health policies are urgently required to mitigate microplastic exposure. Keywords : Microplastics; polyethylene terephthalate (PET); refillable drinking water; environmental health risk assessment; risk quotient